Untitled - Terrence A. Brooks (Information Research: An International Electronic Journal)
Background User scripting heralds a paradigm shift towards web reader empowerment. Powerful web writers of the first decade of the Web needed to be cautioned about usability and accessibility issues. As power shifts to web readers, they become capable of customizing web pages to their own tastes and purposes. This paper describes the development of Greasemonkey extension of the Firefox browser. Argument User scripting is a product of the development of the open source browser, and individual developers who wish to change webpages. The Greasemonkey extension of the Firefox browser permits web readers to write JavaScripts that (1) Change the look and feel of Web pages, (2) Change the functionality of web page controls, and (3) Facilitates Web page 'mashups', hybrid web presentations composed of content from two or more web pages. The only naturally occurring limit to web page modification may be difficult Web page source code. Tools that shield Web readers from the complexity of HTML are being introduced. Conclusion. The paradigm shift to Web readers, armed with powerful and easy-to-use tools for customizing Web pages heralds a new era of the Web. It threatens the idea that a Web page has a single look and feel, and emphasizes the trend to design Web pages as mere input to the reading experience, subject to modification of presentation device as well as reader taste and purpose.